PENERAPAN APLIKASI E-COURT DI PENGADILAN TATA USAHA NEGARA (PTUN) PEKANBARU DITINJAU DARI ASPEK PELAYANAN PUBLIK - Bayu Alif Altarikh; Gusliana HB; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Based on PERMA No. 1 of 2019 concerning Electronic Administration of Casesand Trials in Courts in Article 1 Number 7 states that electronic trials are a series ofprocesses of examining and adjudicating cases by courts carried out with the support ofinformation and communication technology. In this case, the community expects benefitsin implementing or enforcing the law. Because law is for humans, the implementation oflaw or law enforcement must provide benefits or uses for society. The implementation ofE-Court in the Court must provide benefits and convenience in its use, so that the publiccan feel the convenience of public services provided by the Court using this E-Court. Thepurpose of this research is to find out the extent of public service at the StateAdministrative Court in Pekanbaru.The type of research used is sociological legal research. As for the population inthis study are the Chairperson of the Pekanbaru State Administrative Court, the Registrarof the Pekanbaru State Administrative Court, the Pekanbaru State Administrative CourtJudge; Parties Seeking Justice. The research location is at the Pekanbaru City StateAdministrative Court. Data collection techniques using interviews, and literature, withqualitative data analysis.However, the implementation of E-Court still has several drawbacks. First, everyjustice seeker must be able to use existing E-court applications and these electronicdevices must be connected to the internet such as laptops, computers and smartphones.Second, when the application in court itself is disrupted, such as when the application isbeing maintained or the internet or power failure. So electronic registration of cases orE-court cannot be carried out. Third, at the time of the trial, only those registered withthe account who can see the E-court application can see the account at the court, that is,at the time of registration, the one who can see the trial program, if that party forgets theaccount, the trial program cannot be seen by other people.Keywords: State Administrative Court – E-Court -Public Service